Strategies Used in Conveying Knowledge About Political History in the Novel "Destiny: From Shantou to Siam" by S. Deb-Rumphoey - khanthap, wiphap (Asia Pacific Journal of Religions and Cultures, 2024)
The research on Strategies Used in Conveying Knowledge About Political History in the Novel “Destiny: from Shantou to Siam” by S. Deb-Rumphoey proposed to study, via document analysis, strategies and techniques in writing novels that convey political historical knowledge. The researcher employed the qualitative method of examining the texts and techniques used by the author. The results revealed that the author applied 14 strategies in conveying Chinese political history knowledge. These strategies however did not produce the impression that the author was trying to impose knowledge on the reader. On the contrary, the strategies enriched the storyline of the novel. One additional finding showed that the author did not necessarily relate the characters’ thoughts with the Chinese political circumstances of the chosen period in Chinese history.